Elastic-plastic fracture mechanics investigation on two interacting cracks - Lee, Jonathon Zhao Feng (2016)
The author goes through the procedure and steps in deriving the model for the investigation of two interacting Zener-Stroh cracks and an inclusion. In addition, the author also provided results and discussion for each step and found the relations of various parameters of the cracks and the fracture properties. The first step is to find the relationship of a crack and inclusion whereby it is found that the CTOD of the crack will increase with the increase in crack size and the impact of Poisson’s ratio, shear modulus ratio, radius of inclusion, and the crack-inclusion distance on fracture properties was also found. The second step is to find the relationship between crack, inclusion and dislocation whereby the CTOD of the crack will also be affected by an additional dislocation. It is found that the impact will be strongest at a particular angle from the sharp tip of the Zener-Stroh crack. The third step is to find the relationship between two cracks and a circular inclusion. It was being found that an additional crack will have an impact on the fracture properties of the crack. In particular, the CTOD of the existing crack will increase. It is also found that if the two cracks are being separated by a circular inclusion, the CTOD will not be as large as that of the two cracks with no circular inclusion between them. Future work is also suggested for more comprehensive studies of the effect of additional cracks on the existing crack and inclusion as well as cracks position arbitrarily interacting.